Pengujian Kualitas Website menggunakan Metode McCALL Software Quality (studi kasus smkn4bdg.sch.id) - Andrew Suhari Camara M; Khoirida Aelani; Fresa Dwi Juniar S (LPPM STMIK AMIK BANDUNG, 2021)
Internet networking are continues to grow, peoples are familiar with the website. Website can be used for information retrieval and becomes a necessity for the community as information technology develops rapidly, so that the quality of a website becomes important to consider. SMK Negeri 4 Bandung uses the website as a medium in providing information services for the community. The quality of the website of SMK Negeri 4 Bandung has never been done quality testing and it is the background of writing this research. Quality testing in this study using the McCall method. The McCall method aims to improve the quality of software products and websites that are part of the software. McCall has three main perspectives namely Operation products, Revision products and Transition products. The design of quality testing applications in this study uses Java and MySQL databases. The results of this study are recommendations that are expected to become guidelines for developing website quality. Based on research that has been done several recommendations for improvement is the need for improvements to the features that do not work and there should be a monitoring system for the website so that it has a high level of security. After knowing the quality of the overall SMK Negeri 4 Bandung website. Website quality is not good either in the parameters of efficiency, integrity, maintainability, testability, and interoperability. However, website quality is good enough for the parameters of correctness, reliability, usability, flexibility and portability.